COMPETENCY ANALYSIS; GRADUATE DEPARTMENT OF EDUCATION ADMINISTRATION - UPI - DAWOUS, GILANG GUMILANG; SYAFITRI, FAJARINI (EARR (Educational Administration Research and Review), 2018)
Education of Administration programs is one of the discipline study about how to plan and develop all resources. As graduates who pursue education profession, absorption S1 graduates majoring in Educational of Administration has not fully relevant job with its competence. The aim of this study was to obtain a profile of the S1 graduates majoring in Educational of Administration of work in the office and the Department of Education Cimahi and Tutoring Center of Ganesha Operation section Elementary School Marketing Center in Bandung in Three research focus are: 1) Competency Profile S1 Department of Educational Administration in the field of work, 2) Relevance of courses, and 3) self-actualization S1 graduates majoring in Educational Administration. This is a source of research data Cimahi Secretary of Education, Staff Sub-Division and Reporting Program, Section Chief Marketing Promotion and Marketing Staff. The method used is descriptive method with qualitative approach. The data was collected through interviews, observation, and documentation. Based on the findings and analysis in the field that 1) Competence S1 graduates majoring in Educational to Administration can meet the competency areas of work, 2) Subjects Administration Education S1 majoring in accordance with with the field work, and 3) self- Actualization S1 graduates majoring in Educational Administration at field work. The recommendation is based on the results of the empirical findings for: 1) Fulfillment by KKNI Competency Standards, 2) Model Profiles S1 graduates majoring in Educational Administration, 3) Development of programs majoring in Educational Administration, and 4) Optimization of Facility Development Department of Educational Administration.